The Whites of Their Eyes : The Tea Party's Revolution and the Battle over American History - Lepore, Jill, 1966- (Book collections on Project MUSE., 2010)
Asserts that the Tea Party movement prefers to rewrite the history of the American Revolution as anti-intellectual and antipluralist.